The subjective position of a student with intellectual disability in the paradigm of the ecopsychological approach - Tatyana P. Sergiyenko (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper examines the organization of the educational process in Russia of students with intellectual disability from the moment of the allocation of this nosological group, as well as the psychophysiological features of younger schoolchildren with this diagnosis. The problems of the organization of education and upbringing of younger schoolchildren with intellectual disability in the conditions of inclusion are considered. The analysis of statistical data on the number of schoolchildren of 1-9 grades with the diagnosis in question studying in Samara and Samara region under inclusion conditions for four years preceding the study was carried out. The research presents the differences in the development of subjectivity stages of younger schoolchildren with intellectual disability and their peers with the norm of development, identified as a result of diagnostics using the questionnaire of V.I. Panov and A.V. Kaptsov OSS-SP 5, adapted for this category of students. The author concludes that the methodology for determining the stages of subjectivity of younger schoolchildren is available for use by parents of younger schoolchildren in order to foster their dialogical communication with children in order to identify the actual subjectivity stages, as well as to find productive ways to develop the subjectivity of a child in a family environment.